The use of different formulations of tocilizumab in the treatment of patients with moderate to severe COVID-19 - E. I. Veselova; G. D. Kaminskiy; O. V. Lovacheva; B. A. Nanaeva; R. I. Romanov; А. V. Veselov (Туберкулез и болезни лёгких)
The objective of the study: to compare changes in the blood level of C-reactive protein (CRP) during the administration of different formulations of tocilizumab (TCZ) in COVID-19 patients admitted to hospital in real clinical practice.Subjects and methods. The cohort of 14 patients was included in the retrospective study; they all had a severe course of COVID-19 and were admitted to hospital: 7 patients received had intravenous infusions of tocilizumab and 7 had subcutaneous injections. The indication for tocilizumab prescription was the elevation of CRP blood level by 5 times and more or 2-fold and more elevation of ferritin above the norm. In the group receiving subcutaneous injections with tocilizumab, the proportion of elderly people was bigger and CRP levels were higher versus the group receiving intravenous infusions. The efficacy was assessed by changes in CRP levels on the 1st, 3rd and 7th day after the administration. The study included only the patients discharged from hospital with improvement of their state.Results. It has been demonstrated that when the patients develop cytokine storm, the use of both formulations of tocilizumab (for intravenous and subcutaneous administration) is effective. When tocilizumab was administered intravenously, the changes in CRP levels (especially at high rates - more than 150 mg/l) were more intense versus subcutaneous administration. The use of these formulations of tocilizumab had the same long-term efficacy: the level of CRP by the 7th day after administration decreased comparably in both groups, the time of complete normalization of this rate did not differ significantly. The different dynamics of CRP level decrease in each specific case could be associated both with the formulation of the drug and other factors that could not be established.